PEDAGOGIC INFLUENCE OF CHORAL SINGING ON THE FORMING OF A SCHOOLCHILD’S PERSONALITY - Lyubar, R.O. (Pedagogy of Higher and Secondary Education, 2007)
The article considers the issues of a schoolchild’s personality by the means of choral performance. The importance of choral amateur art activities for upbringing of schoolchildren’s moral and development of their aptitude for music is revealed.